2011
DOI: 10.5535/arm.2011.35.4.535
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Early Regular Cardiac Rehabilitation Program on Myocardial Function after Acute Myocardial Infarction

Abstract: ObjectiveTo determine if an early regular cardiac rehabilitation program would have an adverse effect on myocardial function after acute myocardial infarction (AMI).MethodPatients who received percutaneous coronary intervention (PCI) after AMI were divided into the exercise group and control group in accordance with their willingness to participate. Patients in the exercise group (n=18) received ECG monitored exercise for six weeks and were instructed to maintain self exercise in their communities for four mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
3
14
0
2
Order By: Relevance
“…However, it is unclear to what extent the hypertrophic response in the MI-runner group represented an adaptive or maladaptive response, since LV systolic function was not altered by MI, which limits the conclusions about adaptive and maladaptive hypertrophy. These observations concur with previous studies investigating the effect of exercise after MI on the hypertrophic response in rodents (13,14,33) and humans (21,32,56). In contrast, Rengo et al (62) documented increased LV hypertrophy after 10-wk endurance training after MI in mice.…”
Section: H351 Exercise Limits Post-mi Scar Thinningsupporting
confidence: 90%
“…However, it is unclear to what extent the hypertrophic response in the MI-runner group represented an adaptive or maladaptive response, since LV systolic function was not altered by MI, which limits the conclusions about adaptive and maladaptive hypertrophy. These observations concur with previous studies investigating the effect of exercise after MI on the hypertrophic response in rodents (13,14,33) and humans (21,32,56). In contrast, Rengo et al (62) documented increased LV hypertrophy after 10-wk endurance training after MI in mice.…”
Section: H351 Exercise Limits Post-mi Scar Thinningsupporting
confidence: 90%
“…The results on the variable EF showed that different protocols of cardiac rehabilitation cause a significant increase in EF. The results of the research are consistent with the findings of studies conducted by Soleimannejad (11), Ghashghaei (10), Bahremand (34), Sadeghi (4), Basati (9), Schmid (14), and Kim (15). Ejection fraction shows the index of cardiac contractility that is obtained by dividing the stroke volume by the end-diastolic volume (EDV).…”
Section: Discussionsupporting
confidence: 89%
“…Simultaneously, medical administrators can continu- Table 1. Treatment models and characteristics of previous studies Treatment models Researchers Evaluation/monitoring methods Advantages and disadvantages Hospital-based CR Kim (Kim et al, 2011) LVEF It is applicable to a wide range of people; however, it is expensive and time consuming for patients, leading to low patient compliance.…”
Section: Introductionmentioning
confidence: 99%